Macroporous Resin Extraction of Chlorogenic Acid From Eucommia Leaves - Huo, Qing; Mei Gu, Xue (Asian Journal of Chemistry, 2010)
The most suitable absorption of Eucommia chlorogenic acid from Eucommia leaves by macroporous resin has been identified. Ultraviolet spectrometer through a qualitative and quantitative determination, In: l = 330 nm; the standard curve is C = 0.67649 + 21.2607 A; R = 0.9998 and the limited scope: 51 μg/mL < C < 255 μg/mL; six different models of macroporous resins were tested through static adsorption and one macroporous resin labeled as D201 was selected. By dynamic adsorption experiment, adsorption reached saturation time was 80 min; 45 % ethanol with 5.5 bed volume (BV) was found to be able to elute most of the chlorogenic acid adsorbed by the resin. Chlorogenic acid with content of 74.14 % was obtained with the chlorogenic acid recovery of 53.4 % in the purification process Therefore, it is concluded that results in this study may provide scientific references for the large-scale chlorogenic acid production from plants extracts.